Konsep Kafa’ah Maliyah Dalam Perkawinan Suku Bugis Pada Suku Jawa Perspektif Maslahah Mursalah : (Studi Kerukunan Keluarga Sulawesi Selatan) - Hafshah; Fakhruddin; Thoriquddin, Moh (Muhammadiyah University of Surabaya, 2025)
This article discusses the concept of kafa'ah maliyah (economic equality) in the context of inter-ethnic marriage between the Bugis and Javanese communities, focusing on the Kerukunan Keluarga Sulawesi Selatan (KKSS) community in Malang City. This study is motivated by differences in cultural views between the Bugis tribe who emphasize the importance of financial readiness, especially through the practice of